Pemanfaatan Media Sosial Instagram Sebagai Media Pembelajaran Bahasa Jepang - Tia Indriyani; Lisda Nurjaleka (JLA (Jurnal Lingua Applicata), 2023)
Due to the covid-19 pandemic, online platform has made learning more flexible. However, in its implementation, there are obstacles that hinder learning to achieve its goals. Instagram, a social media platform for sharing photos and videos, is one of the most popular social media among millennials. The existence of Instagram as an alternative learning tool makes it possible to supports the achievement of learning objectives, especially language learning. The purpose of this study was to identify the use of social media Instagram as a medium for learning Japanese. This study uses the method of observation and documentation. The data objects are learning content and Instagram features utilization of five content accounts of Japanese language learning creators in Indonesia, namely @auliasenpai, @kejepangan, @harumon.japanese, @jepangeasy and @nihongo.monggo accounts. The results of the study indicate that Instagram social media can be an alternative medium for learning Japanese by utilizing existing Instagram features to create learning content. The types of material themes found in the data are Japanese linguistic, historical and cultural materials. Besides, the introduced Japanese language learning material was diverse, containing linguistic materials which introduce idioms, expressions and several others. These accounts also address JLPT or Noryokushiken test units.